MO710GALECTIN-3, IS IT A NEW PLAYER IN PERITONEAL INFLAMMATION AMONG PATIENTS UNDERGOING PERITONEAL DIALYSIS?. (29th May 2021) - Einbinder, Yael; Cohen-Hagai, Keren; Benchetrit, Sydney; Zitman-Gal, Tali
Abstract: Background and Aims: Peritoneal dialysis (PD) is a common used method for renal replacement therapy. Prolonged PD treatment causes structural and functional changes in the peritoneal membrane which are attributed to local inflammatory process in the peritoneal cavity. Galectin-3 (Gal-3) is a galactoside-binding lectin with pro-inflammatory and pro-fibrotic effects. The aim of this study was to assess correlation between Gal-3 serum and dialysate effluent levels with peritoneal membrane transport characteristics. Method: Gal-3 levels in serum and dialysate effluent were measured simultaneously in prevalent PD patients in morning visit or during peritoneal equilibration test (PET). Gal-3 levels were correlated with clinical and laboratory parameters. Interlukin (IL) -6 levels were measured in dialysate effluent. Gal-3 mRNA and protein expression were evaluated after exposure of primary endothelial cell culture to several dialysate solutions. Results: 37 PD patients were included in the study; mean age was 65.7±13.1 years, mean dialysis vintage was 17.5±13 months. Gal-3 levels in dialysate effluent correlated with peritoneal equilibration test (PET) results (0.663, p=0.005) and effluent IL-6 levels (0.674, p=0.002) but not with serum Gal-3 levels or dialysis vintage. Patients with high PET results had higher effluent Gal-3 levels as compared average low PET results. In multivariate regression analysis effluent IL-6 level was the most dominant predictor of effluent Gal-3 levels. Gal-3 mRNA and protein expression in primary endothelial cell culture were not affected by stimulation with dialysate solutions. Conclusion: Our study demonstrated presence of Gal-3 within the dialysate effluent in PD patients. Gal-3 levels correlated with peritoneal membrane transport characteristics and effluent IL-6 levels suggesting a role in the inflammatory process within the peritoneal cavity.